General Theory and Importance of the Translation Norms - Shohsanam, Dushatova; Zаfаrjon, Djаlolov (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In this article, the general theory of translation reveals the concept of the translation norm, on the basis of which the quality of translation is assessed, in order to ensure the high quality of translation, the translator must be able to compare the text of the translation with the original, evaluate and classify possible errors, make the necessary corrections. If the translator needs to fulfill some requirements, then the assessment of the results of his work will be determined by how fully and successfully he completed these requirements.